The Influence of Self-Esteem and Self-Image In Teenage Learners Sla - Guzal Turaeva (Penerbit Jurnal Indonesia, 2024)
Is age important in teaching second language acquisition? Many scholars try to answer this question and Spanky (1989a) suggests that educational systems usually arrive first at a decision of optimal learning age on political or economic grounds and then seek justification for their decision. From teachers’ point of view, it is crucial to develop a particular method of teaching for a particular age group. This research paper discusses how self-esteem and self-image can influence teen learners, and how teachers can motivate and help them to succeed in learning language